Trade Exports Predict Regional Ballast Water Discharge by Ships in San Francisco Bay - Verna, Danielle E.; Minton, Mark S.; Ruiz, Gregory M. (Frontiers in Marine Science, 2021)
Biological invasions often result from transfers of organisms during trade activities. In coastal ecosystems, commercial ships are a dominant source of species transfers globally, and ships’ ballast water (BW) is a major focus of biosecurity management and policy to reduce invasions. While trade drives shipping patterns, diverse vessel types and behaviors exist such that the quantitative relationship between trade and BW dynamics is still poorly resolved, limiting both science and management. Here, we evaluated a new method to predict BW discharge using trade data, by explicitly considering known BW practices according to vessel and commodity type. Specifically, we estimated the relationship between tonnage of overseas exports and BW discharge volume for San Francisco Bay (SFB), California, as a model system to demonstrate this approach. Using extensive datasets on shipborne exports and BW discharge, we (a) evaluated spatial and temporal patterns across nearly 20 ports in this estuary from 2006 to 2014 and (b) developed a predictive model to estimate overseas BW discharge volume from foreign export tonnage for the whole estuary. Although vessel arrivals in SFB remained nearly constant from 2006 to 2014, associated tonnage of exported commodities more than doubled and BW discharge more than tripled. Increased BW volume resulted from increased frequency and per capita discharge of bulk carriers from Asia and tankers from western Central America and Hawaii, reflecting shifts in direction of commodity movement. The top 11 export commodities (59% of total export tonnage) were transported on bulk carriers or tankers. In a multivariate linear model, annual tonnage of these top 11 export commodities by vessel type were strong predictors of total bay-wide overseas BW discharge (adjusted R2 = 0.92), creating the potential to estimate past or future BW delivery in SFB. Bulk export tonnage provides valuable insights into BW flux, since most BW discharge to ports is driven by trade of bulk commodities and the behavior of bulk and tank ships. BW discharge data are unavailable for many regions and time periods, whereas trade data are widely available and can provide a reliable proxy estimate of BW volume and geographic source, which are both critical to evaluate invasion risk.